Effects of process time on the textural and sensory characteristics of edible bamboo shoots / Aida Firdaus Muhammad Nurul Azmi - Muhammad Nurul Azmi, Aida Firdaus (2005)
Effects of process time on the textural and sensory characteristics on selected edible bamboo shoots were ascertained. Four species of edible bamboo shoots namely buluh brang, bulnh betong, buluh semantan and buluh beting were used. All of them were cut into top and bottom portions. All samples were canned and processed at 25, 35 and 45 minutes at 121°C and 15 psi. The results showed that for top and bottom portions, it was found that buluh semantan showed the hardest texture for fresh bamboo shoots, while buluh beting showed the most softening after being processed at 45 minutes. For sensory characteristics, there were no outstanding preferences for any particular specie. Overall, instrumental texture analysis data showed that the top portion of buluh brang was the hardest or second hardest when fresh or processed at 25 or 35 minutes. No significant preference for hardness was noted, but for fibrousness, buluh brang was significantly preferred to buluh beting and/or buluh betong or buluh semantan. For the bottom portion, buluh brang was either the second hardest or softest based on instrumental texture analysis results. When compared to the sensory data on fibrousness, buluh brang was shown to be significantly preferred at only 25 minutes of process time and no preference was indicated for hardness.